Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan - Abidin, Zainal; Muh. Rahbini (Al-Jadwa: Jurnal Studi Islam, 2022)
The flagship programs of SDIT Al-Rahbini and SDI As-Salam have similarities in the field of tahfidzulqur'anakan but at SDIT As-Salam they have added more students' abilities in the field of writing scientific papers. The purpose of holding these talents is to always explore the talents possessed by students so that they can be developed so that after graduating from this school they can be used as additional skills apart from being proficient in science and social sciences. SDIT Al-Rahbini also prepares superior products that really focus on Qur'anic-based education. This research is a qualitative research conducted using a multiple case study design. The results of this study indicate that (1) the school quality of SDIT Al-Rahbini and As-Salam, namely tahfidzul Qur'an at least 7-9 Juz to graduate from SDIT Al-Rahbini, all activities are based on the Qur'an, in a day carried out 2 waves (hours first: 07.00-08.00 and the second hour: 12.30-13.30), the tahsin model of the Qiroatul Qur'an as a correction for correct and fluent reading, then after the tahsin reading is correct then it is handed over to the Tahfidz teacher of each class, and writing scientific papers. For tahfidz teachers, they must have memorized 30 chapters. In addition, the heads of SDIT Al-Rahbini and SDIT As-Salam have several roles in improving the quality of education, namely educators, managers, administrators, supervisors, leaders (leaders), innovator, motivator.